Extreme multistability in a memristive circuit - Bao, Bo-Cheng; Xu, Quan; Bao, Han; Chen, Mo (Electronics letters, 2016)
A memristive Chua's circuit regarded as a paradigm is reconsidered to exhibit its extreme multistability in this Letter. Memristor initial state-dependent dynamics is analysed and the coexistence of infinitely many attractors related to memristor initial states is revealed by numerical simulations and circuit simulations. The dynamical behaviour just reflects the emergence of extreme multistability in the memristive circuit.